OPTIMALISASI PEMANFAATAN LIMBAH BAJA SEBAGAI BETON BERAT (HIGH DENSITY CONCRETE) - Oka, I Gusti Made (MEKTEK, 2007)
The science increasing, special in particular civil engineering demand of concrete technology of the best.Increasing weight concrete replace of coarce aggregate with steel short. The steel shoert can broughtpresent from repaire shop in city Palu. The dimension of steel short measured of long 30 mm and wide 20mm. The steel short efforted of free corotion, mody and poorly.Preliminary research was to gain Portland cement properties of bulk specific gravity and modulus of finetest. Specimen of fine aggregate properties were bulk specific gravity, water content, water absorption andmodulus of fine. The specimen concrete of cube made with dimension 150 mm x 150 mm x 150 mm.The result of experiment showed of properties of Portland cement between bulk specific gravity and modulusof fine were 3,14 and 5,40%. The result of experiment of properties fine aggregate showed bulk density,water content, bulk specific gravity and fine aggregate absorption were 1,73 t/m3; 0,72%; 2,61 and 0,28%.The result experiment compression strength of high density conrete showed of bulk density and compressionstrength of age 28 days average were 3,96 t/m3and 26,23 MPa